COVID and Cognitive Warfare in Taiwan. (March 2023) - Yu, Max Tsung-Chi; Ho, Karl
In this study, we examine China's cognitive warfare coordinated with military air operations during the COVID pandemic in Taiwan. In May 2021, Taiwan experienced its first novel coronavirus outbreak with up to 500 daily cases. The Chinese government launched a series of coordinated "cognitive warfare" campaigns targeting Taiwan in addition to the People's Liberation Army (PLA) frequent air force incursions into Taiwan's air zone. Meanwhile, through manipulation of the vaccine supply, China turned COVID vaccine into a political issue in Taiwan involving multiple players including pharmaceutical developers, tech giants, and local politicians. Combining multiple sources of data, we analyze the Chinese Government's orchestrated cognitive and information warfare (IW) efforts targeted at influencing the Taiwan public's trust in the Democratic Progressive Party (DPP) government as well as its home-developed vaccine. Identifying the patterns of influencing using cognitive and IW, we found China's ultimate goal was to instill skepticism and confusion in Taiwan's public about the President Tsai Ing-wen's health policy and more generally undermine the creditability of the DPP government.